An Energy-Efficient Multisite Offloading Algorithm for Mobile Devices - Ruifang Niu; Wenfang Song; Yong Liu (International Journal of Distributed Sensor Networks)
Computation offloading is a popular approach for reducing energy consumption of mobile devices by offloading computation to remote servers. Most of the prior work focuses on a limited form of offloading part of computation from a mobile device to a single server. However, with the advent and development of cloud computing, it is more promising for the mobile device to reduce energy consumption by offloading part of computation to multiple remote servers/sites. This paper proposes an Energy-Efficient Multisite Offloading (EMSO) algorithm, which formulates the multiway partitioning problem as the 0-1 Integer Linear Programming (ILP) problem. Moreover, our proposed EMSO algorithm adopts the multi-way graph partitioning based algorithm to solve it. Experimental results demonstrate that our algorithm can significantly reduce more energy consumption as well as execution time and better adapt to the unreliability of wireless networks (such as the network bandwidth changes), compared with the existing algorithms.